2020
DOI: 10.1111/1748-8583.12284
|View full text |Cite
|
Sign up to set email alerts
|

Training and organisational performance: A meta‐analysis of temporal, institutional and organisational context moderators

Abstract: Drawing on systems theory, we conducted a moderated meta‐analysis of the training and organisational performance relationship using 119 primary studies. We examined the moderating effects of quality versus quantity of training, time, institutional and organisational context factors in the relationship between training and organisational performance. Our findings reveal that training is positively and directly related to organisational performance with no statistically significant difference between measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 128 publications
4
88
0
2
Order By: Relevance
“…The complex cause-effect relationships are not linear and require a holistic analysis of all components: actors, relationships, environments, structures, and processes (Weaver-Hightower 2008). Garavan et al (2020) reached the same conclusion with regard to human resource management. Policy implementations may not always lead to the same result -they always involve adaptation processes within the specific framework conditions in a country.…”
Section: B) Motives and Goals Of The Transfersupporting
confidence: 58%
See 1 more Smart Citation
“…The complex cause-effect relationships are not linear and require a holistic analysis of all components: actors, relationships, environments, structures, and processes (Weaver-Hightower 2008). Garavan et al (2020) reached the same conclusion with regard to human resource management. Policy implementations may not always lead to the same result -they always involve adaptation processes within the specific framework conditions in a country.…”
Section: B) Motives and Goals Of The Transfersupporting
confidence: 58%
“…Often it is the sum of the parts, and their interaction, that forms the basis for a successful and sustainable training strategy, both at a micro level (e.g. in a company) (Garavan et al 2020) and at a system level (Pilz 2017, 486). This literature review has revealed that the research of policy transfer moves beyond the learning environments of school and company -it also explores a whole range of transfer elements on various dimensions of the educational eco-system, such as cooperation between stakeholders and the value of vocational training -from various and interconnected academic disciplines (Pilz and Li 2014;Gonon 2014;Pilz 2016aPilz , 2017.…”
Section: B) Motives and Goals Of The Transfermentioning
confidence: 99%
“…These are important new findings, which have not been adequately captured in previous research (Pilz and Wiemann, 2020; Pilz and Li, 2014; Long et al , 1999; Chankseliani et al , 2017). Therefore, the external factors must be given more attention (Garavan et al , 2020). On the basis of the research results we, therefore, have the following implications: The external factors have to be taken into account by companies to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Oyovwe et al, ( 2021) revealed a substantial association between training and work performance. Additionally, quality training will reduce learning durations, encourage training transfer to the workplace, and increase workers' enthusiasm to transmit training results to the organization (Garavan et al, 2020).…”
Section: Motivational Factors and Employee Engagementmentioning
confidence: 99%